Approach of the Natural Sciences in webinars for guidance and coping the pandemic of COVID-19 (Research, Society and Development, 2020)
The advent of the COVID-19 pandemic brought changes to world education thanks to the adoption of measures of social isolation; the use of digital resources proved to be the most viable immediate solution for the continuity of teaching, but there are also problems such as the need for different didactic-pedagogical strategies wieldy of motivating students and teachers. The use of webinars as a complementary communication and guidance resource has proved to be a promising tool. Issues related to living with COVID-19 that combine their discussions with high school curriculum represent an important contribution to the construction of a contextualized knowledge base and, based on this observation, this study proposed to evaluate the presence of contents in the area of ​​natural sciences and its technologies in COVID-19 webinars. A survey with the online video-sharing platform was carried out aiming to search for webinars on COVID-19 containing themes contained in the specific competences of natural sciences and their technologies for high school and how much these items were emphasized. The selection of the videos was made by analyzing what the title, keywords and their summary suggest. Biology, physics and chemistry have a great prominence and expert speakers with extensive experience in the area in which they work and great ability to expose the theme and the ability to clarify doubts have made webinars a valuable motivational approach to specific knowledge related to common national curriculum base - BNCC, as they involve community participation, in different contexts and using different digital technologies in conjunction with the contextual theme COVID-19.